The Comparison of Diabetes Management and Follow-up by Family Medicine or Endocrinology - APAYDIN KAYA, MEMNUNE ÇİĞDEM (My University, 2024)
Objectives: This study aimed to compare the disease management of type 2 diabetes mellitus (T2DM) patients followed up in family medicine (FM) or endocrinology outpatient clinics. Methods: This descriptive study was carried out with T2DM patients who applied to endocrinology and FM outpatient clinics. When analyzing data, patients who only went to endocrinologists (Group 1) and patients who went to both endocrinology and FM or only FM (Group 2) were compared. A questionnaire form (sociodemographic characteristics, education, disease management status, and hemoglobin A1c [HbA1c] levels) was applied to participants. Results: A total of 151 participants were enrolled in the study, with 49 (32.5%) in Group 1 and 102 (67.5%) in Group 2. The median value of HbA1c was 7.5% (2.1%) in Group 1 and 7.1% (2.2%) in Group 2 (p=0.324). Blood glucose measurement abilities and the ability to adjust the insulin dose were higher in Group 1 (47 [95.9%] vs. 75 [73.5%], p=0.001; 22 [44.9%] vs. 15 [14.7%], p<0.001, respectively). However, the frequency of blood pressure measurement, foot examination, and neurological examination was higher in Group 2 (17 [34.7%] vs. 64 [62.7%], p=0.001 for blood pressure measurement; 3 [6.1%] vs. 26 [25.5%], p=0.005 for the foot examination; and 2 [4.1%] vs. 24 [23.5%], p=0.003 for the neurological examination, respectively). Conclusion: While no difference was found in HbA1c levels according to the clinics where the patients were followed, it is noteworthy that blood pressure measurements and foot and neurological examinations were performed more frequently in patients visiting their FMs. Keywords: Diabetes complications, endocrinology, family practice, self-management, type 2 diabetes mellitus
Keywords: Diabetes complications; endocrinology; family practice; self-management; type 2 diabetes mellitus